Intralesional Injection of Bone Marrow Aspirate Concentrate for the Treatment of Osteonecrosis of the Knee Secondary to Systemic Lupus Erythematosus: A Case Report - Kouroupis, Dimitrios; Ahari, Amir F.; Correa, Diego; Shammaa, Riam (Frontiers in Bioengineering and Biotechnology, 2020)
Case: 18-year-old female patient with SLE and corticosteroid-associated extensive bilateral symptomatic knee Osteonecrosis (ON) (Ficat IV), treated with sequential intralesional injections of autologous bone marrow aspirate concentrate (BMAC) under ultrasound guidance. At 3 months, pain was almost absent (VAS) and KOOS/WOMAC showed significant improvement sustained up to 24 months. At 12 months MRI indicated bone maturation, significantly reduced BM edema and subchondral fluid volume, and no collapse/fragmentation signs. Discussion: The clinical and imaging significant improvement observed in this patient suggests that BMAC intralesional injections effectively restored the compromised bone structure. After larger studies, this technique can become an alternative to decompressing surgery for ON cases.